Information systems architecture and technology. proceedings of 37th International Conference on Information Systems Architecture and Technology -- ISAT 2016 /: proceedings of 37th International Conference on Information Systems Architecture and Technology -- ISAT 2016. Part I : ([2016]) - Unknown
No abstract available